Corrosion in Crude Oil Distillation Unit Overhead: A recent Case Study - Ahmed, Ari A. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2021)
Despite all the technological advances and the control mechanisms that exist today to achieve the control of corrosion in overhead systems in atmospheric crude oil distillation units, there is still a high level of difficulty in predicting the phenomenon due to the complexity of the chemical compounds involved in the entire process. The study of this practical case aims to determine what control mechanisms should be optimized in a refinery located in the Autonomous Region of Iraqi Kurdistan to prevent corrosion phenomena’s in this specific system and how it should be done to achieve these improvements. It has been suggested that the corrosion mechanisms by hydrochloric acid and by ammonium chloride have been those that have acted in the operational context of the mentioned facility. To test this hypothesis, a study of the unit’s operational conditions and analytical tests were carried out on the construction material of various components and the products (sediments) found inside the tower. The results show that a lack of control in the salts and sediments content of the feed crude have caused an increase in the hydrolysis process of certain components upstream of the tower and thus the generation of acids and salts was promoted. On this basis, it is necessary to optimize the primary treatment of crude oil and update the chemical treatments and washing water systems to adapt to the new conditions of the feed of the refinery.